2020
DOI: 10.3390/catal10090987
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Catalytic Abatement of N2O Emission in Nitric Acid Plants

Abstract: Different variants for abatement of N2O emission from nitric acid plants with the use of catalysts developed at Łukasiewicz-INS were analyzed. Activity tests on a pilot scale confirmed the high activity of the studied catalysts. A two-stage catalytic abatement of N2O emission in nitric acid plants was proposed: by high-temperature decomposition in the nitrous gases stream (HT-deN2O) and low-temperature decomposition in the tail gas stream (LT-deN2O). The selection of the optimal variant for abatement of N2O em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In contrast, at the highest temperature, i.e., 850 • C, the Co3.5La is significantly more active than the undoped catalyst. Two recent interesting studies on high temperature N 2 O decomposition have shown the significance of parameters such as extrudate size [25] and pressure [27] on N 2 O decomposition. In fact, in measurements carried out at 890 • C with the commercial catalyst [25] it was found that an increase of diameter of the extrudates leads to a decrease of conversions of N 2 O from approx.…”
Section: ) and Lacoo3mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, at the highest temperature, i.e., 850 • C, the Co3.5La is significantly more active than the undoped catalyst. Two recent interesting studies on high temperature N 2 O decomposition have shown the significance of parameters such as extrudate size [25] and pressure [27] on N 2 O decomposition. In fact, in measurements carried out at 890 • C with the commercial catalyst [25] it was found that an increase of diameter of the extrudates leads to a decrease of conversions of N 2 O from approx.…”
Section: ) and Lacoo3mentioning
confidence: 99%
“…Two recent interesting studies on high temperature N2O decomposition have shown the significance of parameters such as extrudate size [25] and pressure [27] on N2O decomposition. In fact, in measurements carried out at 890 °C with the commercial catalyst [25] it was found that an increase of diameter of the extrudates leads to a decrease of conversions of N2O from approx. 80% for 2 mm diameter to 60% for 5 mm extrudates.…”
Section: ) and Lacoo3mentioning
confidence: 99%
See 2 more Smart Citations